AUTHORITARIANISM, PATRONAGE, FAMILY PESANTREN AND ELECTIONS: THE DYNAMICS OF POLITICAL DEMOCRACY IN INDONESIA - Nurul Azizah (RADJA PUBLIKA, 2023)
The Pesantren people's involvement in politics is a new phenomenon regarded as an obstacle to the democratic process and progress. This paper goals to fill the hole in present research on the dominance of the Pesantren humans in nearby politics, which they appear to have strategically mastered. The methodology in this study concerned qualitative data accumulated via commentary techniques, interviews, and documentation. The outcomes have been analyzed, interpreted, and verified. The study aims to prove that the Pesantren family, including chief officials, utilized country facilities and worried about dynastic politics. The find out additionally explores the roles of social, economic, and political capital in election wins. Furthermore, they learn about how dynastic politics has weakened the democratic system and proposes a revision of modern election approaches to ensure fair elections by strengthening election supervision and encouraging voter education.